2004
DOI: 10.1172/jci200421378
|View full text |Cite
|
Sign up to set email alerts
|

Semaphorin 3F, a chemorepulsant for endothelial cells, induces a poorly vascularized, encapsulated, nonmetastatic tumor phenotype

Abstract: Melanoma is the most lethal skin cancer. Most deaths from melanoma result from metastases. Semaphorins have been shown to inhibit neuronal and endothelial cell migration, but the effects of semaphorins on tumor metastasis have not been documented. We found that semaphorin 3F (SEMA3F) was markedly downregulated in highly metastatic human cell lines in vitro and in vivo, which suggested that it may be a metastasis inhibitor. Metastatic human melanoma cells were transfected with SEMA3F and implanted into mice; th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
207
1
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(218 citation statements)
references
References 49 publications
7
207
1
3
Order By: Relevance
“…Sema3F, another inhibitor of angiogenesis, functions as a more global inhibitor in that it blocks angiogenesis in response to both VEGF and bFGF. 28,29 However, as we demonstrate, it does not induce VP (Figure 3). This may be caused by differential binding of these 2 proteins to their Nrp receptors, since Sema3A and Sema3F ligate Nrp-1 and Nrp-2, respectively.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Sema3F, another inhibitor of angiogenesis, functions as a more global inhibitor in that it blocks angiogenesis in response to both VEGF and bFGF. 28,29 However, as we demonstrate, it does not induce VP (Figure 3). This may be caused by differential binding of these 2 proteins to their Nrp receptors, since Sema3A and Sema3F ligate Nrp-1 and Nrp-2, respectively.…”
Section: Discussionsupporting
confidence: 54%
“…However, it inhibits both VEGF-as well as bFGF-induced angiogenesis, indicating that it plays a broader role than Sema3A in regulating blood vessel formation. 28,29 To determine if other class 3 semaphorins can induce VP, we compared the effects of Sema3A, Sema3F, and Sema3B on permeability. Unlike Sema3A, subcutaneous injection of Sema3F or Sema3B did not lead to VP (Figure 3), suggesting that Sema3B and Sema3F are functionally distinct from Sema3A with respect to their influence on the biologic properties of blood vessels.…”
Section: Resultsmentioning
confidence: 99%
“…Sema3F decreases tumor growth in a number of in vivo tumor models, and although Sema3F is capable of interacting with Nrp1, its higher-affinity interaction with Nrp2 appears to be required for its tumor-suppressive activity in many models [58][59][60]. Sema3F exerts a repulsive effect on breast cancer cells [61] and reduces the growth and metastatic activity of colorectal carcinoma cells by modifying integrin αvβ3 [62], suggesting that Sema3F affects tumor cells directly by controlling cell adhesion and migration.…”
Section: Sema3fmentioning
confidence: 99%
“…36,46 More recently it was shown that SEMA3F overexpression in highly metastatic melanoma cells (that only express neuropilin-2 and not neuropilin-1, VEGF-R1 or VEGFR-2) inhibits adhesion and migration but not proliferation. 44 These SEMA3F-transfected melanoma cells injected into nude mice do not become metastatic. All these results suggest that SEMA3F could inhibit endothelial cell invasion and/or tumor cell migration.…”
Section: Classmentioning
confidence: 96%
“…Like Sema3A, Sema3F can inhibit angiogenesis and endothelial cell migration but through neuropilin-2 binding. 44,45 SEMA3F overexpression in mouse fibrosarcoma or ovarian cancer cells block their proliferation. 36,46 More recently it was shown that SEMA3F overexpression in highly metastatic melanoma cells (that only express neuropilin-2 and not neuropilin-1, VEGF-R1 or VEGFR-2) inhibits adhesion and migration but not proliferation.…”
Section: Classmentioning
confidence: 99%